2010
DOI: 10.1519/jsc.0b013e3181c06a0e
|View full text |Cite
|
Sign up to set email alerts
|

Different Profiles of the Aerial Start Phase in Front Crawl

Abstract: Seifert, L, Vantorre, J, Lemaitre, F, Chollet, D, Toussaint, HM, and Vilas-Boas, JP. Different profiles of the aerial start phase in front crawl. J Strength Cond Res 24(2): 507-516, 2010-This study analyzed the kinematics and kinetics (jumping ability) of the aerial start phase in 11 elite front crawl sprinters. The aim was to determine whether a particular start technique leads to a short 15 m start time or whether several start profiles contribute equally well. All swimmers performed 3 starts using their pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 11 publications
1
32
0
2
Order By: Relevance
“…In fact, starting performance seems to be successful as long as initial set positioning is sufficiently close to the preferred backstroke start variant, as previously noticed in rebound jumping (Rodacki & Fowler, 2001). Previous ventral start studies revealed that several similar start styles could lead to similar start performance (Seifert et al, 2010;Vantorre et al, 2014). It is important to note that previous researches considering the start variant with feet parallel and positioned entirely emerged (without wedge) have shown swimmers' CM or hip starting position~0.20 m above the water level Nguyen et al, 2014).…”
Section: Journal Of Sports Sciencessupporting
confidence: 59%
“…In fact, starting performance seems to be successful as long as initial set positioning is sufficiently close to the preferred backstroke start variant, as previously noticed in rebound jumping (Rodacki & Fowler, 2001). Previous ventral start studies revealed that several similar start styles could lead to similar start performance (Seifert et al, 2010;Vantorre et al, 2014). It is important to note that previous researches considering the start variant with feet parallel and positioned entirely emerged (without wedge) have shown swimmers' CM or hip starting position~0.20 m above the water level Nguyen et al, 2014).…”
Section: Journal Of Sports Sciencessupporting
confidence: 59%
“…Previous studies have been reinforcing the idea that swimmers can perform backstroke start during entry and underwater phase guided by a common motor strategy to achieve similar performance, irrespective of the variation adopted (Rodacki & Fowler, 2001;Seifert et al, 2010). Moreover, it had already been observed that the differences noticed among start variations tended to disappear once immersion is completed (Vantorre et al, 2014).…”
Section: Variablesmentioning
confidence: 82%
“…Studies lacking analysis on biomechanical advantages/disadvantages when using different foot and hand set-up positions for backstroke start make it hard to choose a start variation for training and competition (Seifert et al, 2010). Despite the set-up position adopted, one could expect that backstrokers would reveal different motor profile organisation to achieve similar 15-m start time (Rodacki & Fowler, 2001;Seifert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters like the reaction time (temporal delay from the start signal until the first mechanical expression) and the impulse on the block (integral of force in order to time) seem to assume relevance in the production of an effective start (Vantorre, Seifert, Fernandes, Vilas-Boas, Chollet, 2010). There are some biomechanical studies that focus on the start as a whole: block phase, flight, entry in water, underwater glide, leg kicking and swimming phase Seifert et al, 2010;Vilas-Boas, Fernandes, 2003), but few did an exhaustive analysis of the block phase (Honda, Sinclair, Mason, Pease, 2012;Kibele, Biel, Fischer, 2013), defined by the time between the start signal and the instant the swimmer loses the contact of his feet with the block .…”
Section: Introductionmentioning
confidence: 99%